2020
DOI: 10.3389/fcell.2020.602837
|View full text |Cite
|
Sign up to set email alerts
|

REX-001, a BM-MNC Enriched Solution, Induces Revascularization of Ischemic Tissues in a Murine Model of Chronic Limb-Threatening Ischemia

Abstract: Background: Bone Marrow Mononuclear Cells (BM-MNC) constitute a promising alternative for the treatment of Chronic Limb-Threatening ischemia (CLTI), a disease characterized by extensive blockade of peripheral arteries, clinically presenting as excruciating pain at rest and ischemic ulcers which may lead to gangrene and amputation. BM-MNC implantation has shown to be efficient in promoting angiogenesis and ameliorating ischemic symptoms in CLTI patients. However, the variability seen between clinical trials mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…These models allow us to follow-up cell mobilization in response to ischemia [36][37][38][39]. Moreover, biodistribution assays are essential to determine the cell's fate [40,41] and more importantly, to evaluate the biosafety profile, being required by regulatory guidelines prior to initiating cell therapy into the clinic [42]. Furthermore, for treatments testing human components such as human cells, immunosuppressed animals (nude, athymic, etc.)…”
Section: Animal Models Of CLImentioning
confidence: 99%
See 3 more Smart Citations
“…These models allow us to follow-up cell mobilization in response to ischemia [36][37][38][39]. Moreover, biodistribution assays are essential to determine the cell's fate [40,41] and more importantly, to evaluate the biosafety profile, being required by regulatory guidelines prior to initiating cell therapy into the clinic [42]. Furthermore, for treatments testing human components such as human cells, immunosuppressed animals (nude, athymic, etc.)…”
Section: Animal Models Of CLImentioning
confidence: 99%
“…Schematic representation of femoral artery ligation (FAL) strategies usually applied to create PAD/CLI models, from the lowest (left) to the highest (right) severity models of the disease. A representative image of the FAL strategy followed in our research group is also shown [41,47]. Legend: 1 Iliac artery, 2 Iliacofemoral artery, 3 Internal iliac artery, 4 Pudendoepigastric trunk, 5 Femoral artery and its branches (lateral circumflex and proximal caudal), 6 Superficial caudal epigastric artery, 7 Popliteal artery, and 8 Saphenous artery.…”
Section: Animal Models Of CLImentioning
confidence: 99%
See 2 more Smart Citations
“…Perfusion was expressed as the ratio of left (ischemic) vs. right (non-ischemic) limbs. In parallel, ischemic symptoms (motility changes, inflammation, ulceration, and necrosis) were registered during the entire experiment using the Tarlov score (motility changes) [28], together with ischemic and modified ischemic scores [29] used in CLI animal models, as described [31] (Supplementary Table S1).…”
Section: Follow-up Of Physiological Changes After CLI and Cell Administrationmentioning
confidence: 99%